2016
DOI: 10.1007/s13205-015-0314-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of photosynthetic efficacy and CO2 removal of microalgae grown in an enriched bicarbonate medium

Abstract: Bicarbonate species in the aqueous phase is the primary source for CO2 for the growth of microalgae. The potential of carbon dioxide (CO2) fixation by Chlorella pyrenoidosa in enriched bicarbonate medium was evaluated. In the present study, effects of parameters such as pH, sodium bicarbonate concentration and inoculum size were assessed for the removal of CO2 by C. pyrenoidosa under mixotrophic condition. Central composite design tool from response surface methodology was used to validate statistical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Therefore, our result suggests that bicarbonate and CO2 can be used alternatively with similar effect on biomass growth of algae. In some studies, bicarbonates as an inorganic carbon source gave higher biomass and lipid production (Abinandan andShanthakumar 2016, Mokashi et al 2016).…”
Section: Growth Of T Wisconsinensis: Od Measures Microalgae Cell Gromentioning
confidence: 99%
“…Therefore, our result suggests that bicarbonate and CO2 can be used alternatively with similar effect on biomass growth of algae. In some studies, bicarbonates as an inorganic carbon source gave higher biomass and lipid production (Abinandan andShanthakumar 2016, Mokashi et al 2016).…”
Section: Growth Of T Wisconsinensis: Od Measures Microalgae Cell Gromentioning
confidence: 99%
“…It should be noted though that the optimal range of nutrients (NO 3 − and PO 4 −3 ) lies outside the range of experiment values. The lack of fit test with p value of 0.05 showed that the model is satisfactorily fitted with the experimental design data (Abinandan and Shanthakumar 2016).…”
Section: Biomass Productivitymentioning
confidence: 97%
“…To overcome the mass transfer limitation and acidification of CO 2(g) , the carbonates produced from CO 2(g) can be used as an alternative inorganic carbon source . Several studies have been conducted using bicarbonate as a carbon source for the growth of microalgae . The microalgae potential of CO 2 fixation by Chlorella pyrenoidosa in bicarbonate enriched medium was reported with the maximum CO 2 removal of 86.32% and accumulation of 4.61 mg/L chlorophyll content at pH 8 with sodium bicarbonate concentration of 3.33 g/L .…”
Section: Microalgae and Its Carbon Source—a Biological Co2 Mitigationmentioning
confidence: 99%
“…Several studies have been conducted using bicarbonate as a carbon source for the growth of microalgae . The microalgae potential of CO 2 fixation by Chlorella pyrenoidosa in bicarbonate enriched medium was reported with the maximum CO 2 removal of 86.32% and accumulation of 4.61 mg/L chlorophyll content at pH 8 with sodium bicarbonate concentration of 3.33 g/L . The chlorophyll content of microalgae Chlorella vulgaris cultivated in NaHCO 3 (1.125 g/L) supplemented wastewater was increased up to 9.6 mg/L and the nutrient (Nitrate) removal efficiency was 13.5% better compared with 2% CO 2(g) as a carbon source .…”
Section: Microalgae and Its Carbon Source—a Biological Co2 Mitigationmentioning
confidence: 99%